Genome mining for deciphering potential biocontrol action modes of Bacillus licheniformis TRQ32 against wheat (Triticum turgidum subsp. durum) phytopathogenic fungi - Karem María Figueroa-Brambila; Amelia C. Montoya-Martínez; Ixchel Campos-Avelar; Fannie Isela Parra-Cota; Sergio de los Santos-Villalobos (Discover Sustainability)
Abstract Strain TRQ32 was isolated from wheat (Triticum turgidum L. subsp. durum) rhizosphere in a commercial field located in the Yaqui Valley, Mexico. Its draft genome was sequenced using Illumina NovaSeq technologies, resulting in a genome size of 4,363,473 bp with 45.8% G + C content; 878,209 bp N50; 2 L50 and 28 contigs. Based on phylogenomic analysis [the 16S rRNA gene (similarity: 100%), Overall genome relatedness indexes (OGRIs) (OrthoANI: 99.58%, and GGDC: 96.40%), and whole-genome phylogenetic tree construction], strain TRQ32 was affiliated to Bacillus licheniformis. Genomic annotation revealed 4833 coding DNA sequences (CDS) across 334 subsystems, indicating genes involved in stress response (42 CDS); virulence, disease, and defense (39 CDS); iron acquisition (43 CDS); as well as secondary metabolism (11 CDS). Additionally, AntiSMASH 7.1 identified three biosynthetic gene clusters (BGCs) associated with biocontrol activity: lichenysin, bacillibactin, and lichenicidin. In vitro biocontrol assays showed that B. licheniformis TRQ32 inhibited the mycelial growth of eight wheat phytopathogenic fungi belonging to the genera Bipolaris, Cladosporium, Fusarium, Alternaria, and Curvularia, by over 50%. This study highlights the taxonomic affiliation and biocontrol potential of B. licheniformis TRQ32 through genome sequencing, annotation, and mining. The findings demonstrate that the native bacterial strain TRQ32 is a promising strategy to control wheat phytopathogenic fungi by manly bacillibactin biosynthesis, which contributes to sustainable agricultural practices.